Close Reduction Technique for Severely Displaced Radial Neck Fractures in Children - Shah, Maulin M. (Indian J Orthop, 2020)
INTRODUCTION: Radial neck fractures account for 5–10% of paediatric elbow trauma. Radial neck fractures have been classified by Judet into five types (I–IVb). There is a global agreement to reduce radial neck fractures with angulation more than 30° (Type III, IVa and IVb). Various maneuvers have been described but none of them uniformly achieved complete reduction in severely displaced radial neck fractures (Type IVa and Type IVb Judet). In this case series, we are presenting our experience with close reduction of ten severely displaced paediatric radial neck fractures to achieve complete anatomical reduction. METHODS: We attempted close reduction in ten consecutive children with average age of 8.59 ± 1.68 years (range, 6–12 years) who presented with severely displaced radial neck fracture (Type IVa and IVb Judet). There were five girls. All patients had close injuries and presented to us within 24–48 h. One of the patients had associated undisplaced lateral condyle fracture. We have excluded two patients with associated elbow dislocation. Close reduction was performed within 48 h of initial injury. RESULTS: We were able to obtain complete anatomical reduction in all of our patients with this technique. None of the patients required fixation of fracture. At 1 year of follow-up, (12 ± 2.07 months, range 9–16 months) all patients demonstrated almost full range of elbow and forearm motion. Final radiographs revealed complete union without any evidence of avascular necrosis. CONCLUSION: This technique offers an option of close reduction for the most severely displaced radial neck fractures, which were otherwise being treated by surgical intervention. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s43465-020-00168-6) contains supplementary material, which is available to authorized users.